An examination of Alzheimer’s disease and white matter from 1981 to 2023: a Bibliometric and visual analysis - Wu, Linman; Jin, Liuyin; Li, Lixia; Yu, Kai; Wu, Junnan; Lei, Yuying; Jiang, Shulan; He, Jue (Frontiers in Neurology, 2023)
Background Alzheimer’s disease (AD) is characterized by the presence of gray matter lesions and alterations in white matter. This study aims to investigate the research related to white matter in the context of AD from a Bibliometric standpoint. Methods Regular and review articles focusing on the research pertaining to Alzheimer’s disease (AD) and white matter were extracted from the Web of Science Core Collection (WOSCC) database, covering the period from its inception to 10th July 2023. The “Bibliometrix” R package was employed to summarize key findings, to quantify the occurrence of top keywords, and to visualize the collaborative network among countries. Furthermore, VOSviewer software was utilized to conduct co-authorship and co-occurrence analyses. CiteSpace was employed to identify the most influential references and keywords based on their citation bursts. The retrieval of AD- and white matter-related publications was conducted by the Web of Science Core Collection. Bibliometric analysis and visualization, including the examination of annual publication distribution, prominent countries, active institutions and authors, core journals, co-cited references, and keywords, were carried out by using VOSviewer, CiteSpace, the Bibliometrix Package, and the ggplot2 Package. The quality and impact of publications were assessed using the total global citation score and total local citation score. Results A total of 5,714 publications addressing the intersection of Alzheimer’s disease (AD) and white matter were included in the analysis. The majority of publications originated from the United States, China, and the United Kingdom. Prominent journals were heavily featured in the publication output. In addition to “Alzheimer’s disease” and “white matter,” “mild cognitive impairment,” “MRI” and “atrophy” had been frequently utilized as “keywords.” Conclusion This Bibliometric investigation delineated a foundational knowledge framework that encompasses countries, institutions, authors, journals, and articles within the AD and white matter research domain spanning from 1981 to 2023. The outcomes provide a comprehensive perspective on the broader landscape of this research field.